Dimensional measurement calibration of dial calipers based on JIS B 7507: 2016 standard in the measurement laboratory - Manurung, Agnes Br; Purba, Adi Syahputra; Manalu, Ari Angga; Juwita, Erna; Aryswan, Adhe (Trigin Publisher, 2025)
Dial calipers are very frequently used by both measurement laboratories and production. Dial calipers need to be calibrated every 12 months. The purpose of this study is to provide an understanding of how to calibrate a dial caliper, using a method based on JIS B 7507:2016 Standard. The JIS standard itself provides guidance and reference for dial caliper calibration. Based on the calibration results obtained, it is known that the dial caliper has deviation or error values in each measurement (outside, inside, depth, and step) with values of 0.0200 mm and -0.01000, referring to an accuracy of +/-0.03mm. After evaluation based on the standard, these error values still meet the requirements of JIS B 7507-2016. The benefit of this calibration is dial calipers are important to calibrate both before and after use to ensure optimal accuracy and consistent measurement results and also this calibration performed is sufficiently valid and reliable.